2018
DOI: 10.1029/2018jd028727
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Liquid Cloud Microphysical Properties of Deep Convective Systems: 2. Parameterization of Raindrop Size Distribution and its Application for Convective Rain Estimation

Abstract: The liquid cloud microphysical properties for stratiform rain (SR) have been investigated in Part 1 of this series. Since convective rain (CR) has characteristics in raindrop size distribution (DSD) and precipitation that are distinct from SR, we investigate the CR properties in this study by using 20 hr of CR samples collected by 17 Automatic Parsivel Units disdrometers during the Midlatitude Continental Convective Clouds Experiment over the Atmospheric Radiation Measurement Southern Great Plains site. A full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…As shown in previous studies (e.g., Wang et al, 2015Wang et al, , 2016Wang et al, , 2018Feng et al, 2012Feng et al, , 2019, the minimum reflectivity of the 3-D mosaic NEXRAD dataset is 0 dBZ (Fig. 2a).…”
Section: Mapping the Radar Observations To The Model Gridsupporting
confidence: 84%
“…As shown in previous studies (e.g., Wang et al, 2015Wang et al, , 2016Wang et al, , 2018Feng et al, 2012Feng et al, , 2019, the minimum reflectivity of the 3-D mosaic NEXRAD dataset is 0 dBZ (Fig. 2a).…”
Section: Mapping the Radar Observations To The Model Gridsupporting
confidence: 84%
“…The surface DSD measurements could be described by the three‐parameter gamma distribution (Brandes et al, 2004; J. Wang et al, 2015; Kozu & Nakamura, 1991; Smith, 2003; Ulbrich, 1983; J. Wang, Dong, & Xi, 2018; Zhang et al, 2001). The mathematical form of the gamma distribution is as follows: N()D=N0DμeitalicλD, where D (mm) is the volume equivalent diameter of a raindrop and N ( D ) (m −3 mm −1 ) is the number concentration of raindrops at volume equivalent diameter D per unit diameter range.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the possible mismatches between the CSA classification and radar‐derived precipitation due to surface wind, the grid boxes that were classified as SR but had PRs greater than 10 mm/hr have been excluded from the analysis for SR. The 10‐mm/hr threshold is often used to discriminate convective precipitation (Han et al, ; Leary & Houze, ; Penide et al, ; Wang et al, ), and previous studies have found that less than 3% of rain rates classified as stratiform are above the 10‐mm/hr threshold (Wang et al, ). The total precipitation amount of pixels having rain rates greater than 10 mm/hr account for less than 8% of the total stratiform precipitation amount in our analysis.…”
Section: Methodsmentioning
confidence: 99%